A new P, S‐coordinating ferrocenyl ligand: synthesis of a precursor and its coordination compounds with PdII and PtII. Issue 5 (23rd April 2014) - Mouas Toma, Nardjes; Daran, Jean‐Claude; Merazig, Hocine; Manoury, Eric
<x xml:space="preserve">Abstract</x> In our ongoing development of ferrocene ligands, 1‐dimethylamino‐2‐(diphenylphosphinothioyl)ferrocene is being used as a convenient building block to obtain racemic or enantiomerically pure ligands. Using this building block in large excess allowed the formation of several by‐products, two of which have already been reported; the structure of a third by‐product, namely 1‐(diphenylphosphinothioyl)‐2‐{[(diphenylphosphinothioyl)sulfanyl]methyl}ferrocene, [Fe(C5H5)(C30H25P2S3)], is presented here. The crystal structure is built up from a ferrocene unit, with one of the cyclopentadienyl (Cp) rings substituted in the 1‐ and 2‐positions by a protected diphenylphosphinothioyl group and a [(diphenylphosphinothioyl)sulfanyl]methyl fragment, –CH2SP(=S)Ph2. There are C—H...S interactions which result in the formation of chains parallel to the c axis. After desulfurization, the crude material was then reacted with Pd and Pt (M) precursors [MCl2(CH3CN)2] to yield two isostructural dinuclear complexes arranged around twofold axes, namely (R, R/S, S)‐bis{μ‐[2‐(diphenylphosphanyl)ferrocen‐1‐yl]methanethiolato‐κ3P, S:S}bis[chloridopalladium(II)] pentane disolvate, [Pd2{Fe(C5H5)(C18H15PS)}2Cl2]·2C5H12, and the platinum(II) analogue, (R, R/S, S)‐bis{μ‐[2‐(diphenylphosphanyl)ferrocen‐1‐yl]methanethiolato‐κ3P, S:S}bis[chloridoplatinum(II)] toluene monosolvate, [Pt2{Fe(C5H5)(C18H15PS)}2Cl2]·C7H8, in which the two metal atoms present a slightly distorted square‐planar geometry formed by two bridging S atoms and P and Cl atoms. The P, S‐chelating ligand results from the rupture of one of the P—S bonds in the starting ligand. These dinuclear complexes display a butterfly geometry. Surprisingly, only the (R, R/S, S) diastereoisomer has been isolated.